The Molecular Genetics of Autosomal Recessive Nonsyndromic Intellectual Disability: a Mutational Continuum and Future Recommendations. (15th November 2016) - Khan, Muzammil Ahmad; Khan, Saadullah; Windpassinger, Christian; Badar, Muhammad; Nawaz, Zafar; Mohammad, Ramzi M
Summary: Intellectual disability (ID) is a clinical manifestation of the central nervous system without any major dysmorphologies of the brain. Biologically it affects learning capabilities, memory, and cognitive functioning. The basic defining features of ID are characterized by IQ<70, age of onset before 18 years, and impairment of at least two of the adaptive skills. Clinically it is classified in a syndromic (with additional abnormalities) and a nonsyndromic form (with only cognitive impairment). The study of nonsyndromic intellectual disability (NSID) can best explain the pathophysiology of cognition, intelligence and memory. Genetic analysis in autosomal recessive nonsyndrmic ID (ARNSID) has mapped 51 disease loci, 34 of which have revealed their defective genes. These genes play diverse physiological roles in various molecular processes, including methylation, proteolysis, glycosylation, signal transduction, transcription regulation, lipid metabolism, ion homeostasis, tRNA modification, ubiquitination and neuromorphogenesis. High‐density SNP array and whole exome sequencing has increased the pace of gene discoveries and many new mutations are being published every month. The lack of uniform criteria has assigned multiple identifiers (or accession numbers) to the same MRT locus (e.g. MRT7 and MRT22). Here in this review we describe the molecular genetics of ARNSID, prioritize the candidate genes in uncharacterized loci, and propose a new nomenclature to reorganize the mutation data that will avoid the confusion of assigning duplicate accession numbers to the same ID locus and to make the data manageable in the future as well.